Effect of interfacial conductivity on electrical characteristics of negative capacitance field effect transistors - Y G Xiao; K C Kang; L Y Tian; K Xiong; G Li; M H Tang; Z Li (Materials Research Express, 2021)
In this article, an interfacial conductivity model for the surface potential and the drain current was proposed based on the metal-interface-ferroelectric-insulator-semiconductor (MIFIS) structure negative capacitance field effect transistor (NC-FET). The simulating results illustrate that the electrical conductivity ( σ ) of the interface layer between the electrode and ferroelectric thin film caused by lattice misfit plays an important role in the process of voltage amplifying and steep switching for the NC-FET. It is indicated that new device design rules should take into account this scenario.